Conflicts in the role of business as a social partner in the South African economy : a study of skills development in the Border-Kei region - Delport, Kandi Sue (Rhodes University, Faculty of Humanities, Department of Sociology, 2014)
This thesis analyses conflicts in the role of business as a social partner in the South African economy by studying skills development in the Border-Kei Region. Skills development is a key component of the South African government's programme of labour market regulation and is founded on a participatory approach. The skills development framework requires the participation and co-operation of multiple social partners but relies heavily on the role of business in the attainment of national and sectoral skills development objectives. Unfortunately, however, there are significant conflicts in the role which business is expected to play which consequently hinder the efficiency of the framework and the likelihood that that these objectives will be realised. One of the most pertinent examples of these conflicts is the voluntary nature of the skills development framework, which incentivises but does not compel organisations to invest in training and development. Other conflicts include dissonances between national and employer led strategies and organisational disincentives to engage in training and development. This qualitative study uses an interpretive approach to study how and to what extent the Skills Development Act is implemented in selected organisations in Buffalo City as well as studying the issues pertaining to the implementation process. By using a purposive sampling approach, this research includes both primary data in the form of semi-structured interviews and secondary data in the form of documentary sources. The data represents the perspectives of business, labour and government and provides significant depth of insight into the discussions and issues surrounding skills development in Buffalo City. This dissertation argues that South Africa's vocational training system, institutionalised through appropriate legislation, may not be sufficient to mobilise social partners, and of primary concern in this research "“ business "“ to invest in skills development. It suggests that extensive reliance on business is an insufficient way in which to upskill the labour market. However, with few alternatives to this approach, it is subsequently essential that business is encouraged to buy into the collective interest of skills development objectives. This primarily entails overcoming the challenges that embody the framework and increasing state emphasis on skills development.
Keywords: Social responsibility of business -- South Africa; Industries -- Social aspects -- South Africa; Conflict management -- South Africa; Occupational training -- South Africa -- Eastern Cape; Human capital -- South Africa -- Eastern Cape; Economic development -- South Africa -- Eastern Cape; Labor laws and legislation -- South Africa -- Eastern Cape